The impact of the product attributes on consumer choices of toothpaste - Sathana, V. (University of Sri Jayewardenepura, 2011)
Today increasing competition and rivals supply create more confusion for the selection of suitable product for the consumers. Product attributes usually comprise features, functions, benefits, and uses and they create a meaningful difference in a brand's performance. The objectives of this paper were to identify the relationship and impact of product attributes on consumer choice and to find out significant difference between personal characteristics on consumer choices. Data was collected from the primary source of questionnaires; the population of this study was toothpaste consumers form Nallur, Division. The convenient sample selection was based on demographic and economic variables on different age, sex, job, education, income, family size and life style of that population. Three hundred subjects participated in the experiment. Five critical attributes quality, product variety, price, branding and packaging affecting choice were all perceived equal across brands. Researcher adopted quantitative analysis as, correlation and regression analysis using statistical package (SPSS). This study produced 6 major findings: first, product attributes had taken significant impact on consumer choice, second, quality and product variety of tooth paste created important impact on consumer choice, third, price and Packaging were another important influencing factor of consumer choice, fourth, product branding was also influencing some extent in the selection. Fifth there was positive correlation between product attributes and consumer choices, sixth family income and education characteristic of consumer were more influenced on the consumer choices. Toothpaste Product institution must create innovative and creative attributes changes to succeed in the dynamic and competitive world.
Keywords: Product Attributes; Consumer Choice; Demographic and Economic Variables